2015
DOI: 10.1186/s13018-015-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Osmolarity influences chondrocyte repair after injury in human articular cartilage

Abstract: BackgroundThe purpose was to determine the influence of irrigation solution osmolarity on articular chondrocytes survival and metabolic state following mechanical injury.MethodsOsteochondral explants were harvested from patients undergoing total knee arthroplasty for osteoarthritis and then cut through their full thickness to establish mechanical injury models. Cartilage explants were incubated in irrigation solutions (saline and balanced salt) with different osmolarities (180, 280, 380, 580 mOsm/L) for 2 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Sixteen studies met the inclusion criteria and were included in this review. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] This number is inclusive of the studies found after screening the reference sections of the initial studies ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies met the inclusion criteria and were included in this review. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] This number is inclusive of the studies found after screening the reference sections of the initial studies ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Six of the sixteen included studies compared the results of irrigation solutions that had differing osmolarities. 18,[20][21][22][23][24] One out of the six studies 20 that analyzed irrigation fluids during canine shoulder arthroscopy found no statistically significant differences between normal saline and a hyperosmolar irrigation fluid when examining changes in shoulder girth, tissue water content, or chondrocyte viability. The remaining five studies found superiority with hyperosmolarity.…”
Section: Influence Of Osmolaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Inwieweit dies durch die Art der Spülflüssigkeit und Abkühlungseffekte vermittelt wird, bedarf noch weiterer Abklärung. Interessanterweise konnten hyperosmolare arthroskopische Spüllösungen bei akuten Knorpelschädigungen Zelltod und Proteoglykanverlust reduzieren [57,60]. Weiterhin wurden für hyaluronsäurehaltige Präparate oder plättchenreiches Plasma, die am Ende einer Arthroskopie appliziert wurden, positive Effekte beschrieben [61,62].…”
Section: Beeinflussung Der Gelenkhomöostase Durch Eine Arthroskopischunclassified
“…A study reported the weight gain of patients with hypertonic irrigation was 2.25 ± 0.77 kg and the use of hypertonic lavage did not increase operating time [27]. Studies also have shown isotonic or hypotonic extracellular uid might aggravate the death of chondrocytes in articular cartilage [28]. In contrast, hypertonic lavage uid had a protective effect on articular cartilage [29].…”
Section: Discussionmentioning
confidence: 99%